A key centriole assembly interaction interface between human Plk4 and STIL appears to not be conserved in flies - Cottee, M; Johnson, S; Raff, J; Lea, S (Company of Biologists, 2017)
A small number of proteins form a conserved pathway of centriole duplication. In humans and flies, the binding of Plk4/Sak to STIL/Ana2 initiates daughter centriole assembly. In humans, this interaction is mediated by an interaction between the Polo-Box-3 (PB3) domain of Plk4 and the coiled-coil domain of STIL (HsCCD). We showed previously that the Drosophila Ana2 coiled-coil domain (DmCCD) is essential for centriole assembly, but it forms a tight parallel tetramer in vitro that likely precludes an interaction with PB3. Here we show that the isolated HsCCD and HsPB3 domains form a mixture of homo-multimers in vitro, but these readily dissociate when mixed to form the previously described 1:1 HsCCD:HsPB3 complex. In contrast, although Drosophila PB3 (DmPB3) adopts a canonical polo-box fold, it does not detectably interact with DmCCD in vitro Thus, surprisingly, a key centriole assembly interaction interface appears to differ between humans and flies.